Exo-Autoethnography: An Introduction - Denejkina, Anna (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2017)
Exo-autoethnography is the autoethnographic exploration of a history whose events the researcher does not experience directly, but a history that impacts the researcher through familial, or other personal connections, by proxy. It is an approach to research and autoethnographic writing that seeks to analyze individual and private experience, as directed by the other's experience or history, to better understand: a history that affects the researcher indirectly; and personal and community experience as it relates to that history. The method of exo-autoethnographic research and writing has been developed for the qualitative study into transgenerational transmission of trauma, moving beyond the personal experience of the researcher. In this first and preliminary conception, the method aims to connect the present with a history of the other through transgenerational transmission of trauma and/or experiences of an upbringing influenced by parental trauma.